Digitalisasi dan Pengembangan Sistem Informasi Pendidikan - Vina Widia Afriani; Muhammad Irwan Padli Nasution (Yayasan Salam Cerdas Al-Fattah, 2025)
The development of educational information systems has become an essential requirement for enhancing the effectiveness, efficiency, and overall quality of the teaching and learning process. Through the implementation of such systems, educational institutions are able to manage academic data, administrative processes, and institutional communication in an integrated manner. This article aims to analyze the concepts, methods, and outcomes of implementing information system development within the context of modern education. Using a qualitative approach based on a literature study, the research identifies various forms of information system innovations applied in educational institutions and examines their impact on the quality of educational services. The findings reveal that the implementation of information systems in educational settings has produced significant positive effects, particularly in accelerating data management processes, thereby enabling administrative activities to run more efficiently and systematically. Transparency has also improved because academic and managerial information is presented openly and can be easily accessed by all stakeholders. Moreover, institutional accountability is strengthened through more organized documentation systems that allow clear tracking of every process. Ultimately, the effectiveness of learning is enhanced through digital support that enables educators and learners to access materials, assessments, and academic services in a more structured and purposeful manner.